Modelos descontínuos na análise tridimensional do comportamento hidromecânico de fundações de barragens de betão - Azevedo, Nuno Monteiro (2022)
This paper presents the formulation and results of the application of two three-dimensional discontinuum models that simulate the hydromechanical interaction. In these models the mechanical behaviour is simulated in a similar way but the hydraulic behaviour is simulated using two different approaches. The first model is based on a formulation in which seepage takes place through two-dimensional interface elements. The second model, which is proposed in this paper, is based on a unidirectional discretization and a network of seepage channels. The hydromechanical models implemented in the computational module Parmac3D-Fflow are verified and validated using simple examples, and the model proposed is calibrated so that the same water pressures and discharges are obtained with both models. A hydromechanical model of a dam/foundation system was developed, taking into account the existence of a grout curtain and a drainage system within the dam foundation. The advantages of the model proposed in the study of the hydromechanical behaviour of dam foundations are highlighted.